1956
DOI: 10.1152/ajplegacy.1956.185.1.185
|View full text |Cite
|
Sign up to set email alerts
|

Water Balance of the Camel

Abstract: Camels ( Camelus dromedarius) were exposed to prolonged periods of water deprivation during winter, spring and summer in the Sahara desert. Determinations were made of: weight changes, water and food intake, urine flow and concentrations, plasma concentrations, etc. It was found that the camel can tolerate a loss of water corresponding to 30% of its body weight even when exposed to the severe desert heat. Other mammals dehydrated in a hot environment may die from circulatory failure already when the water loss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

1958
1958
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(43 citation statements)
references
References 0 publications
1
42
0
Order By: Relevance
“…The results show that 1) lactating camels drank in anticipation of coming water deficits when water was offered at 4-or 8-day intervals but not enough to compensate body weight losses after 16 days water deprivation; 2) dehydrated lactating camels actively searched shade despite rectal temperature below 35°C; 3) plasma sodium concentration and osmolality increased after 4 days and, after 8 days, total plasma protein and vasopressin concentrations also increased; and 4) it took a long time for the lactating 4 812 16 1 4 812 16 1 4 812 16 1 4 812 camels to restore body fluid homeostasis after 16 days of water deprivation. Drinking huge amounts of water to rapidly replenish body weight loss in the camel was described about 50 years ago (36), and later the black Bedouin goat was shown to immediately drink amounts of water compensating a 40% loss of its body weight (38). Storage of the consumed water in the forestomach and gut, saliva buffering the forestomach contents, and the continuous exchange of electrolytes and water between gastrointestinal tract and blood plasma are important factors that explain the exceptional tolerance to water deprivation in camels and ruminants (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…The results show that 1) lactating camels drank in anticipation of coming water deficits when water was offered at 4-or 8-day intervals but not enough to compensate body weight losses after 16 days water deprivation; 2) dehydrated lactating camels actively searched shade despite rectal temperature below 35°C; 3) plasma sodium concentration and osmolality increased after 4 days and, after 8 days, total plasma protein and vasopressin concentrations also increased; and 4) it took a long time for the lactating 4 812 16 1 4 812 16 1 4 812 16 1 4 812 camels to restore body fluid homeostasis after 16 days of water deprivation. Drinking huge amounts of water to rapidly replenish body weight loss in the camel was described about 50 years ago (36), and later the black Bedouin goat was shown to immediately drink amounts of water compensating a 40% loss of its body weight (38). Storage of the consumed water in the forestomach and gut, saliva buffering the forestomach contents, and the continuous exchange of electrolytes and water between gastrointestinal tract and blood plasma are important factors that explain the exceptional tolerance to water deprivation in camels and ruminants (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…For example, many desert ungulates significantly reduce the rate of cutaneous and respiratory water loss when dehydrated (Maloiy, 1973;Schmidt-Nielsen et al, 1956), indicating that neuroendocrine integration is used to balance heat and water loss. We found that elephants are able to modulate water loss when evaporation potential is greatest (high WVPSD) (Fig.7).…”
Section: The Skin and Control Of Cewlmentioning
confidence: 99%
“…The dromedary camel (Camelus dromedarius) is an important livestock species uniquely adapted to hot arid environments by its ability to reduce water loss through feces, urine, and evaporation (Bekele et al, 2013;Ben Goumi et al, 1993;Robertshaw and Zine-Filali, 1995;Schmidt-Nielsen et al, 1956). With increasing human population and inadequate food production in Africa and parts of Asia, it is important to develop semi-arid and arid rangelands through appropriate livestock production systems, and the camel is a natural choice (Schwartz and Dioli, 1992).…”
Section: Introductionmentioning
confidence: 99%